Pengaruh Kepuasan Kerja dan Kerjasama Tim Terhadap Produktivitas Karyawan dengan Motivasi Kerja Sebagai Variabel Intervening (Studi pada Momo Jaya Aluminium) - Laila Mukhlisatul Izza; Kasnowo Kasnowo; Rini Armin (Indo Publishing, 2026)
This study addresses the issue of employee productivity at Momo Jaya Aluminium. Company data indicates that the defect rate rose from 7% during the 2022–2025 period to 9% in the most recent timeframe. This situation is attributed to weak teamwork and low job satisfaction, factors that have negatively impacted overall motivation and productivity. The study aims to examine the influence of job satisfaction and teamwork on employee productivity—both directly and indirectly through motivation as an intervening variable—among Momo Jaya Aluminium employees. A quantitative research method was employed, involving a population of 105 individuals. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) via the SmartPLS software. The results demonstrate that job satisfaction and teamwork have a positive and significant effect on employee productivity, both directly and indirectly through work motivation as an intervening variable.